What's Next? Judging Sequences of Binary Events. [article]. - Oskarsson, An T.
The authors review research on judgments of random and norandom sequences involving binary events with a focus on studies documenting gambler's fallacy and hot hand beliefs. The domains of judgment include random devices, births, lotteries, sports performances, stock prices and others. After discussing existing theories of sequence judgments, the authors conclude that in many everyday settings people have naive complex models of the mechanisms they believe generate observed evevts, and they rely on these models for explanations, predictions and other inferences about event sequences. The authors next introduce an explanation-based, mental models framework for describing people's belief about binary sequences, based on 4 perceived characters of the sequence generator : randomness, intentionality, control and complexity. Furthermore, they propose a Markov process framework as a useful theoretical notation for the description of mental models and for the analysis of actual event sequences.-- (from the author)